Dufour and Soret Effects on Melting from a Vertical Plate Embedded in Saturated Porous Media - Basant K. Jha; Umaru Mohammed; Abiodun O. Ajibade (Journal of Applied Mathematics)
Thermal-diffusion and diffusion-thermo effects on combined heat and mass transfer in mixed convection boundary layer flow with aiding and opposing external flows from a vertical plate embedded in a liquid saturated porous medium with melting are investigated. The resulting system of nonlinear ordinary differential equations is solved numerically using Runge Kutta-Fehlberg with shooting techniques. Numerical results are obtained for the velocity, temperature, and concentration distributions, as well as the Nusselt number and Sherwood number for several values of the parameters, namely, the buoyancy parameter, melting parameter, Dufour effect, Soret effect, and Lewis number. The obtained results are presented graphically and in tabular form and the physical aspects of the problem are discussed.